A multi-party verifiable quantum proxy signature scheme based on quantum teleportation - Wang, Chengxiang; Lu, Dianjun; Tian, Fuyao; Yao, Weixin (Journal of applied physics, 2024)
With the development of science and technology and the appearance of various special conditions that cause signers to be unable to sign, proxy signature is gradually becoming a hot spot in cryptography research. This paper combines proxy signature, quantum teleportation, and multi-party verification and proposes a multi-party verifiable quantum proxy signature scheme based on quantum teleportation. This scheme has the following characteristics: The authentication method based on the H a s h function can effectively solve the problem of identity identification among members; in order for the proxy signer to be able to verify the correctness of the proxy authorization, a form of proxy signature authorization that concatenates the identity information of the original signer is used. The security analysis shows that our scheme is unforgeable and undeniable and can resist intercept-resend attacks and cheating attacks.